BACTERIOCIN ACTIVITY OF LACTOBACILLUS FROM NATURAL SOURCES AND DNA FINGERPRINTING BY RAPD -PCR - PRASAD.M.P. (International Journal of Pharma and Bio Sciences, 2014)
Lactobacillus species are most widely used as probiotics and as starter cultures in the food industry. In recent years bacteriocin producing Lactobacillus have attracted significant attention. In this study Lactobacillus sps were isolated from different natural sources and indentified on the basis of biochemical and physiological characteristics according to Bergey’s manual of determinative bacteriology. Bacteriocin was isolated from all the Lactobacillus samples and their antibacterial activity were checked against S aureus. The bacteriocin from sample 1 showed maximum zone of inhibition (16 mm). The Genomic DNA of the Lactobacillus sps was isolated by Phenol –chloroform extraction method and RAPD –PCR was performed by generation of DNA fingerprint. Out of 10 primers used OPX 8 primer produced most distinguishable band pattern with total of 118 bands with 8-21 bands per sample.